Meningkatkan Aktivitas Dan Hasil Belajar Muatan IPA Materi Siklus Hidup Hewan Dengan Mengunakan Model Baiman Dan Media Diorama Pada Kelas IV Di SDN Gambut 8 - Aulia Aziza; Sulaiman (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research aims to describe teacher activities, student activities and student learning outcomes regarding animal life cycles after implementing the Baiman learning model (PBL, TGT and PaP) and diorama media. This research uses Classroom Action Research. The target of the research is class IV students at SDN Gambut 8, even semester of the 2022/2023 academic year. From the results of the analysis, it was found that teacher activities at meetings I, II, and II received scores of 24, 26, and 30. Student activities at meetings I, II, and II obtained percentages of 67%, 77%, and 89%. Student learning outcomes at Meeting I for cognitive aspects reached 39%, affective 56% and psychomotor 50%. Meeting II cognitive aspects obtained a percentage of 61%, affective 72% and psychomotor 78%. Meeting III cognitive aspects reached 83%, affective 94% and psychomotor 89%. The conclusion of this research is that the Baiman model and diorama media can increase student activity and learning outcomes. The results of this research can be used as a reference to improve student activities and learning outcomes in science content.